Enterovirus D68–Associated Acute Flaccid Myelitis in Immunocompromised Woman, Italy - Giombini, Emanuela; Rueca, Martina; Barberi, Walter; Iori, Anna Paola; Castilletti, Concetta; Scognamiglio, Paola; Vairo, Francesco; Ippolito, Giuseppe; Capobianchi, Maria Rosaria; Valli, Maria Beatrice (Emerging infectious diseases, 2017)
In Italy in 2016, acute flaccid myelitis developed in a woman who had received a hematopoietic stem cell transplant. Enterovirus D68 viral genome was detected in respiratory and cerebrospinal fluid samples, and the viral protein 1 sequence clustered with lineage B3. Immunocompromised adults may be at risk for enterovirus D68-associated neurologic complications.